Serum homocysteine levels predict poor recovery and relapse in first-attack myelin oligodendrocyte glycoprotein antibody disease - Li, Yanfei; Jia, Yanjie (Frontiers in Neurology, 2025)
Background and objectiveMyelin oligodendrocyte glycoprotein antibody disease (MOGAD) is an inflammatory demyelinating disease with a high risk of recurrence and progressive disability, and it is crucial to find sensitive and reliable biomarkers for prognosis and the early prediction of relapse. In the study we investigated whether serum homocysteine (Hcy) levels are associated with a poor prognosis or risk of relapse in patients with first-attack MOGAD.MethodsWe enrolled patients diagnosed as having first-attack MOGAD between January 2019 and December 2024 in this retrospective study. Clinical data and initial Expanded Disability Status Scale (EDSS) scores were collected and analyzed. Clinical outcomes were measured using the final EDSS score and relapse events. We used logistic regression models and Cox regression analysis to determine the association between Hcy levels and clinical recovery and relapse.ResultsSeventy patients (female, n = 36; male, n = 34) with first-attack MOGAD were included in this study. The final EDSS scores (p = 0.015) and relapse rates (p = 0.039) were higher in the high Hcy group than in the normal Hcy group. Multivariate analysis results indicated that Hcy levels [odds ratio (OR) 1.126; 95% confidence interval (CI) 1.005–1.261, p = 0.04] and the initial EDSS scores (OR 2.017, 95% CI 1.266–3.214, p = 0.003) were independent risk factors for predicting poor recovery. Kaplan–Meier survival analysis showed that Hcy levels were a predictor of relapse in patients with MOGAD (log-rank test p = 0.029). The results of the multivariate Cox proportional hazards model indicated that Hcy levels [hazard ratio (HR) 1.088, 95% CI 1.020–1.161, p = 0.011] were related to MOGAD relapse.ConclusionWe identified Hcy levels as an independent risk factor for predicting poor clinical recovery in patients with first-attack MOGAD. Hcy levels were also significantly associated with the relapse of MOGAD.